Unexpectedly high stability and surface reconstruction of PdAuAg nanoparticles for formate oxidation electrocatalysis. Issue 21 (21st May 2020) - Pan, Bowei; Chen, Fuyi; Kou, Bo; Wang, Junpeng; Tang, Quan; Guo, Longfei; Wang, Qiao; Li, Zhen; Bian, Weiqi; Wang, Jiali
Abstract : Pd3 Au3 Ag1 NPs on carbon nanotubes undergo a potential-driven surface reconstruction that improves the activity and durability for the electrocatalytic formate oxidation reaction. Abstract : High-performance Pd-based nanocatalysts for alkaline methanol and formate fuel cells have stimulated widespread attention. Hence, a series of ternary Pd–Au–Ag nanoalloys have been synthesized on carbon nanotubes, which demonstrate promising activity and unexpectedly high stability for the formate oxidation reaction (FOR) in alkaline medium. The ternary Pd3 Au3 Ag1 nanoalloy catalyst showed an initial mass activity of 4.51 A mgPd −1 and a retained mass activity of 1.32 A mgPd −1 after chronoamperometric measurement for 3600 s, which are superior to the best values for all FOR catalysts reported so far. The Pd3 Au3 Ag1 catalyst also showed a good specific activity of 4.32 mA cm −2 for the methanol oxidation reaction. Furthermore, surface reconstruction of the Pd3 Au3 Ag1 nanoalloy was observed during FOR, where the activity of Pd3 Au3 Ag1 catalysts increased up to 33% and the cycling durability retained 55% after cyclic voltammetry with the upper potential of 1.7 V. The FOR enhancement is attributed to the formation of mixed oxidation-state Ag sites and the increase in the Pd surface coverage, and provides a new prospect for the design of ternary nanoalloy electrocatalysts for various fuel oxidation reactions.